IMPLEMENTATION OF LEARNING STATIONS TO ENHANCE READING COMPREHENSION SKILLS (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study examines the implementation of Learning Station strategy for enhancing students' reading comprehension abilities, with particular focus on identifying main ideas and drawing conclusions from texts. The research employed a classroom action research design involving 33 eleventh-grade vocational high school students in Karawang. Data collection utilized diagnostic tests, classroom observations, and questionnaires. Findings demonstrated a significant transformation in students' reading comprehension levels following the Learning Station intervention. The proportion of students at the literal comprehension level decreased markedly from 27% to 3%, while those achieving the evaluative level increased from 16% to 70%. The Learning Station approach effectively facilitated students' progression through Westwood's reading comprehension hierarchy, enabling them to develop critical thinking skills in analyzing hortatory exposition texts. This research contributes to the literature on effective reading instruction strategies and provides practical insights for educators facing challenges in developing students' reading comprehension abilities.